(untitled) (Journal of the College of Basic Education, 2023)
Research abstract:The current research aimed to identify the tendencies of students in Iraqi schools towards mathematics. The descriptive survey approach was adopted for the research, and the research sample consisted of (300) students from the sixth grade of the general directorates of education of Baghdad / Rusafa (first, second, third), and Karkh (first, second, third), and they were chosen randomly. For the second semester of the academic year (2021-2022). Then, the preparation of the research tool, which is: a questionnaire to measure tendencies towards mathematics, consisting of (17) items, and using the alpha-Cronbach equation. The value of the stability coefficient for the scale was (0.876). The results showed a high percentage of students’ inclinations towards mathematics in general, as the percentage of students’ total inclinations reached (87.21%), while the first domain of the orientation scale achieved the lowest percentage of (81.90%), while the second domain achieved the highest percentage among the domains of the scale. amounted to (92.51%), and several recommendations were reached, the most important of which is the diversity in teaching methods and methods used in presenting educational content that develop the desires of students and lead to their attraction and increase their interaction, participation and motivation towards learning and their correct acquisition of mathematical conceptsKeywords: tendencies